Study on Taman Warisan Melayu as a heritage attraction. - Mohamed Hairul Borhan. (2008)
The motivation for this study was the success of Chinatown which could be replicated for the Taman Warisan Melayu (TWM). The main target market for TWM is local Malay youths who play an important role in ensuring the continuity of the Malay heritage. Knowing this ensures marketing efforts focus on the right group of individuals. Surveys and in-depth interviews were then conducted to identify factors that would attract and encourages repeat visits. Finally, feasible recommendations were made to attract more youths to the heritage centre as a way to ensure that they keep the Malay heritage alive in Singapore.